EFEKTIVITAS REALISASI DAN SERAPAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA KABUPATEN OGAN KOMERING ILIR TAHUN 2013-2015 - Nur Afnijaya Trisnawati; Burhanuddin Burhanuddin; Ika Sasti Ferina (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
The aim of this research was to assess the realization effectiveness and uptake of Anggaran Pendapatan dan Belanja Daerah (APBD) government at Ogan Komering Ilir in 2013-2015 has been implemented to achieve the desired goals yet. The method used in this research was descriptive quantitative by comparing the budget Laporan Realisasi Anggaran (LRA) from 2013-2015 at Ogan Komering Ilir district.The results of this study can be concluded that the realization of the Budget (APBD) has been performing well, but the average realization and uptake in Pendapatan Asli Daerah (PAD), other legitimate income and financing revenue area is not performing well or ineffective. This is because the available funds are not comparable to the program that will be conducted.